2020
DOI: 10.3389/fphar.2020.00852
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Potential Use of Medicinal Plants From Asteraceae and Lamiaceae Plant Family in Cardiovascular Diseases

Abstract: Cardiovascular diseases are one of the most prevalent diseases worldwide, and its rate of mortality is rising annually. In accordance with the current condition, studies on medicinal plants upon their activity on cardiovascular diseases are often being encouraged to be used in cardiovascular disease management, due to the availability of medicinal values in certain dedicated plants. This review was conducted based on two plant families, which are Asteraceae and Lamiaceae, to study on their action in cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 106 publications
0
78
1
3
Order By: Relevance
“…Also, catechin amounts were found at high levels in the present study (1,299.4±7.52 µg/mg-5,796.9±8.12 µg/mg). Though Michel et al (2020) indicated that kaempherol glycosides are the main phenolic in the Asteracea, but present study showed that the major phenolic compound of T. densum taxa is catechin. Similarly, Gecibesler et al (2016) found that catechin was a principal component of Tanacetum.…”
Section: Resultscontrasting
confidence: 67%
“…Also, catechin amounts were found at high levels in the present study (1,299.4±7.52 µg/mg-5,796.9±8.12 µg/mg). Though Michel et al (2020) indicated that kaempherol glycosides are the main phenolic in the Asteracea, but present study showed that the major phenolic compound of T. densum taxa is catechin. Similarly, Gecibesler et al (2016) found that catechin was a principal component of Tanacetum.…”
Section: Resultscontrasting
confidence: 67%
“…Moreover, extracts of Asteraceae plants showed high efficiency in the treatment of diabetes, inflammations, etc. [ 25 ], and also in cardiovascular-related diseases [ 26 ]. This highly diverse family is mainly distributed in Europe and the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…etc.) demonstrated potential cardioprotective activity of the extracts, based on the antioxidant properties of high polyphenols content [ 30 ].…”
Section: Introductionmentioning
confidence: 99%